Recuentos cromosómicos en compositae de colombia (1984)
Eighty-six chromosome counts of Compositae are reported from differentprovinces of Colombia. Twenty-four are first counts from the genusPlagiocheilus (Astereae), and from species in Achyrocline, Aspilia, Baccharis, Calea, Eupatorium, Hieracium, Liabum, T agetes, Verbesina, Vernonia and We delia. Additional counts are also provided for 62 populations of taxa counted previously of which nine are new numbers. The systematic significance of certain of these counts is discussed.